PELATIHAN MINDFULNESS UNTUK MENURUNKAN TINGKAT STRES PADA SISWI KELAS X - Ulfa Noor Laili Uswatun Hasanah; Siti Muthia Dinni (Jurnal Psikohumanika, 2020)
This study aims to determine the effect of mindfulness training to reduce the stress levels of 7 students in SMK X Pundong who have moderate to severe stress levels. The stress level was measured using the DASS scale. This research is categorized into experimental research type with one group pretest-posttest design. The data obtained were then analyzed using the non-parametric Wilcoxon test method to see the difference between students’ stress levels before and after the intervention through the IBM SPSS Statistics 25 for windows program. The results showed that there were significant differences in students’ stress levels before and after the intervention was given with a value of p = 0.018 (p <0.05). This proves that mindfulness training can reduce the stress levels of students in class X.